2020
DOI: 10.1111/petr.13864
|View full text |Cite
|
Sign up to set email alerts
|

Unmanipulated haploidentical hematopoietic stem cell transplantation for children with myelodysplastic syndrome

Abstract: Myelodysplastic syndrome (MDS) is a rare childhood disease, with an annual incidence of 1 to 4 cases per million. This accounts for less than 5% of all pediatric hematological malignancies. 1,2 Low-grade MDS [refractory cytopenia of childhood (RCC)] and advanced MDS [refractory anemia with excess blasts (RAEB) and RAEB in transformation (RAEB-T)] are the most recent pediatric MDS classifications. Allogeneic hematopoietic stem cell transplantation (allo-HSCT) is the only curative option currently available for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…In a Chinese registry study (CBMTRG) of 454 patients with MDS who underwent allo-HSCT, the 4-year CIR (6%, 7% and 10%, p = 0.36) and DFS (58%, 63% and 71%, p = 0.14) were comparable between the 3/6 HID-, 4–5/6 HID- and MSD-HSCT patients [ 43 ]. Suo et al also demonstrated that HID-HSCT in pediatric patients with MDS improved 3-year DFS (81.9%) [ 44 ].…”
Section: Indications and Timing Of Allo-hsctmentioning
confidence: 99%
“…In a Chinese registry study (CBMTRG) of 454 patients with MDS who underwent allo-HSCT, the 4-year CIR (6%, 7% and 10%, p = 0.36) and DFS (58%, 63% and 71%, p = 0.14) were comparable between the 3/6 HID-, 4–5/6 HID- and MSD-HSCT patients [ 43 ]. Suo et al also demonstrated that HID-HSCT in pediatric patients with MDS improved 3-year DFS (81.9%) [ 44 ].…”
Section: Indications and Timing Of Allo-hsctmentioning
confidence: 99%
“…The haploSCT cohorts with AML, MDS, or Ph+ ALL, including haplo-cord-HSCT, had higher CMV viremia than the HLA-matched HSCT cohorts (16)(17)(18)(19), but the incidence of CMV disease was not significantly different between the two groups. Even in pediatric patients with MDS or patients with relapsed/ refractory acute lymphoblastic leukemia after CAR-T therapy who underwent haploSCT, the incidence of CMV reactivation/ infection was less than 60%, and very few patients developed CMV disease (20,21).…”
Section: Incidence Of Cytomegalovirus Infection After Haplosctmentioning
confidence: 99%
“…At present, the disease can be treated by hematopoietic stem cell transplantation, etc. (4). While owing to its high incidence and mortality, it is urgent to understand the pathogenesis of MDS and find new therapeutic targets from many angles.…”
Section: Introductionmentioning
confidence: 99%